Management of interruptions to fractionated radiotherapy treatments: Four and a half years of experience. Issue 12 (December 2016) - de la Vega, J.M.; Ríos, B.; del Río, J. Torres; Guerrero, R.; Castillo, I.; Guirado, D.
Highlights: A program was developed to manage treatment interruptions. Two measures to reduce OTT prolongation and improve treatment outcomes are studied. Compensation program has a significant result on HN or prostate cancer patient. Working on public holidays assists in the meeting of international recommendations. Abstract: Background and purpose: The study objective was to report our four-and-a half years experience (March 1 2011–August 15 2015) of a program to manage interruptions in fractionated radiotherapy treatments. Methods: A program was developed, based on a specific database, to manage treatment interruptions. Benefits of the program were analyzed in reference to previously published data. Analysis was also performed of two measures to reduce OTT prolongation and improve treatment outcomes: working on public holidays and conducting treatment unit maintenance on Saturdays. Results: The study included 2352 patients. Patients with head and neck cancer obtained the greatest benefit from the program, with a mean increase in TCP of 3.5% and a benefit of at least 4% in 45.6% of them. In prostate cancer patients, the likelihood of biochemical failure was reduced by a mean of 2.0% and was reduced by at least 4% in 19.7% of them. Application of the two proposed measures would have improved the TCP by a mean of 5.4% in head and neck cancer patients. The impact of the compensations program and proposed measures is lesser in the remaining cancer types studied. Conclusions: Implementation of a compensation program has a significant impact on patients with head and neck or prostate cancer but OTT prolongation remains excessive in many treatments. The introduction of fractions on public holidays would assist in the meeting of recommendations for these patients.